2010
DOI: 10.1063/1.3503154
|View full text |Cite
|
Sign up to set email alerts
|

On the assumed impact of germanium doping on void formation in Czochralski-grown silicon

Abstract: The assumed impact of Ge doping on void formation during Czochralski-growth of silicon single crystals, is studied using scanning infrared microscopy. It has been reported that Ge doping leads to a reduction in the flow pattern defect density and of the crystal originated particle size, both suggesting an effect of Ge on vacancy concentration and void formation during crystal growth. The present study however reveals only a marginal-if any-effect of Ge doping on grown-in single void size and density. Double an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…N doping strongly suppressed V‐type point defect clusters despite the increased total concentration of V. Abe recently investigated heavily doped FZ‐Si and found that Sn and Sb doping leads to more V‐rich crystals while B and C doping leads to more I‐rich crystals. Vanhellemont et al reported that Ge doping at 1 × 10 20 Ge cm −3 of CZ‐Si has only a limited impact on V concentration.…”
Section: Impact Of Doping On the Voronkov Criterionmentioning
confidence: 99%
See 1 more Smart Citation
“…N doping strongly suppressed V‐type point defect clusters despite the increased total concentration of V. Abe recently investigated heavily doped FZ‐Si and found that Sn and Sb doping leads to more V‐rich crystals while B and C doping leads to more I‐rich crystals. Vanhellemont et al reported that Ge doping at 1 × 10 20 Ge cm −3 of CZ‐Si has only a limited impact on V concentration.…”
Section: Impact Of Doping On the Voronkov Criterionmentioning
confidence: 99%
“…Abe made a similar observation in FZ‐Si for 5 × 10 16 C cm −3 . Vanhellemont et al reported that Ge doping at 1 × 10 20 Ge cm −3 in CZ‐Si has only a small impact on the V concentration. The calculated results shown in Fig.…”
Section: Impact Of Doping On the Voronkov Criterionmentioning
confidence: 99%
“…These impurities interact with vacancies and interstitials, and can therefore be used to affect interactions of point defects during crystal growth, during device processing as well as under irradiation. Although a huge amount of experimental and theoretical data have been collected during the last decades, our understanding of intrinsic point defect‐impurity reactions is not yet definitive, see, for example 1–9 and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…More than 15 papers were jointly published in international journals and conferences (see e. g. Refs. [66][67][68][69]). Jan visited Deren's lab 9 times.…”
Section: Oxygen Precipitationmentioning
confidence: 97%